Halide-assisted single-crystal-morphology high-nickel ternary layered positive electrode material and preparation method thereof
By introducing halide as dopants and sintering flux in the preparation process of single crystal morphology high-nickel ternary layered cathode material, the lattice defects and particle adhesion problems of the material during the sintering process are solved, and the structural stability and electrochemical properties of the material are significantly improved.
Patent Information
- Application Number
- CN202510261168.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-06-03
AI Technical Summary
The existing single crystal morphology high nickel ternary layered cathode materials have problems such as lattice defects, particle adhesion agglomeration, poor dispersion, poor rate performance and cycle stability during the preparation process.
The high-temperature solid-phase sintering method is used as dopant-assisted high-temperature solid-phase sintering method. By regulating the heating rate and cooling rate of the multi-step calcining stage, low-melting halides are introduced as sintering flux and dopants to reduce the sintering temperature and promote the growth and dispersion of single crystal particles.
The structural stability and electrochemical properties of the material are improved and the cycle stability is enhanced. The discharge capacity of the first circle is greater than 200mAh g-1, and the capacity retention rate after 200 circles is greater than 93%, which is suitable for large-scale production.
Smart Images

Figure CN120089707A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of cathode materials, and particularly relates to a halide-assisted single-crystal morphology high-nickel ternary layered cathode material and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy vehicle industry in recent years, people's demand for the driving range of electric vehicles has been increasing day by day. In order to better meet the industrialization needs, it is urgent to research and develop high-energy density lithium-ion batteries. The high-nickel ternary layered cathode material is considered to be one of the most promising next-generation high-energy density lithium-ion battery cathode materials in the material market due to its advantages such as high energy density, good cycle performance, and excellent rate performance.
[0003] Currently, the commercially available high-nickel cathode materials are mainly polycrystalline morphology high-nickel ternary layered cathode materials. While increasing the nickel content can improve the capacity, it will reduce its cycle stability and thermal stability. This is because at high delithiation states, the primary particles generate anisotropic crystal volume changes, causing local stress accumulation, which will induce mechanical stress inside the secondary particles, leading to the rupture of the secondary particles. Subsequently, the electrolyte penetrates in, and the new surfaces exposed by the particle fragmentation will repeat this adverse phase change, gradually resulting in the ultimate failure of the material. The single-crystal morphology high-nickel ternary layered cathode material can well avoid the problem of particle microcracks in the secondary particles, and its pore-free structure advantage provides higher mechanical strength. Therefore, the material has excellent structural stability, electrochemical performance, and thermal stability during the cycling process.
[0004] The most common preparation methods for single-crystal morphology high-nickel ternary layered cathode materials are as follows: (1) High-temperature solid-state sintering method: Mix the high-nickel ternary precursor of nickel, cobalt, and manganese and the lithium source evenly, and then prepare single-crystal particles through high-temperature sintering. However, in order to obtain larger micron-sized single-crystal particles, higher sintering temperatures and longer holding times are required, which will cause serious lattice defects in the material. Moreover, the prepared single-crystal particles often have problems such as adhesion and agglomeration of primary particles, poor dispersion, uneven particle size distribution, and poor rate performance and cycle stability. (2) Flux-assisted sintering method: Introduce a flux (such as LiCl, NaCl, KCl, Li 2 SO 4 、Na 2 SO 4 、K 2 SO 4 etc.) that can form a eutectic point with lithium to participate in the chemical reaction, promote the growth of single-crystal particles, and prepare single-crystals with a relatively high degree of dispersion under the action of solid-state sintering. However, the flux needs to be washed repeatedly with water and reheated, which will cause capacity loss and structural reorganization of the material, and the process is complex and the cost is high.
[0005] For example, Patent CN109768231 uses a mixed molten salt and a nickel cobalt manganese hydroxide precursor for high-temperature calcination, and at the same time regulates the ratios of the precursor to the molten salt, the inorganic salt to the Li compound, to obtain a single-crystalline high-nickel ternary cathode material with good crystallinity and excellent electrochemical performance. However, the additional water washing step inevitably complicates the process and increases the cost, resulting in surface structure phase change and capacity loss. Patent CN118270857 uses pre-oxidation sintering and optimizes the sintering platform, doping a compound with a large surface area to promote the co-directional growth of crystals. The obtained single-crystalline high-nickel cathode material needs to be crushed and sieved, and the uncontrollable mechanical crushing will cause irreversible effects on the crystal structure of the high-nickel material. Patent CN116553627 uses an inorganic oxide dopant to assist multi-stage sintering, reduces the duration of high-temperature sintering, promotes the uniform nucleation of single-crystalline particles, and improves the electrochemical performance of the high-nickel single-crystalline cathode material. However, for the single-crystalline high-nickel ternary layered cathode prepared in the above patents, in the voltage range of 2.7 - 4.3V and under the rate condition of 0.5C, its electrochemical performance has a capacity retention rate of only 95% after 50 cycles, which is difficult to meet the requirements of the current long driving range of electric vehicles.
[0006] In summary, there are some problems in the preparation of the single-crystalline high-nickel ternary layered cathode material in the prior art, resulting in poor electrochemical performance and high energy consumption of the material. Summary of the Invention
[0007] Object of the Invention: The first object of the present invention is to provide a halide-assisted single-crystalline high-nickel ternary layered cathode material, which stabilizes the crystal structure of the material and improves the electrochemical performance of the material; the second object of the present invention is to provide a preparation method of the halide-assisted single-crystalline high-nickel ternary layered cathode material, which reduces the material cost and production energy consumption.
[0008] Technical Solution: The halide-assisted single-crystalline high-nickel ternary layered cathode material of the present invention has the chemical formula; Li 1-α Ni x Co y Mn z A α O 2-β X β, where 0.6 ≤ x < 1, 0 < y ≤ 0.2, 0 < z ≤ 0.2, 0 < α ≤ 0.05, 0 < β ≤ 0.05, x + y + z = 1, A is at least one of Li, Na, K, Rb, Cs, and X is at least one of F, Cl, Br, I; the material has a monodisperse morphology; the primary sintering conditions during the sintering process of the material are: heating at a heating rate of 1.5 - 10 °C / min to 200 - 600 °C, pre-sintering for 1 - 5 h, then heating at a heating rate of 5 - 20 °C / min to 600 - 850 °C, sintering for 5 - 20 h, and finally, cooling to room temperature at a rate of 1 - 20 °C / min; the dopant and flux during the sintering process are halide salts.
[0009] Preferably, the halide salt is A-X, where A is at least one of Li, Na, K, and X is at least one of F, Cl, Br.
[0010] Preferably, during the sintering process of the material, first heat at a heating rate of 1.5 - 10 °C / min to 430 - 550 °C and pre-sinter for 3 - 5 h, then heat at a heating rate of 5 - 10 °C / min to 700 - 800 °C and sinter for 8 - 15 h; the cooling rate during the final cooling process is 2 - 10 °C / min.
[0011] Preferably, the average particle size of the single-crystal morphology high-nickel ternary layered cathode material is 1 - 3 μm.
[0012] The preparation method of the halide-assisted single-crystal morphology high-nickel ternary layered cathode material of the present invention includes the following steps:
[0013] (1) Mix the nickel-cobalt-manganese ternary precursor with a lithium source and a halide salt evenly by a high-speed ball mill to obtain a mixture;
[0014] (2) Place the mixture in a tube furnace, under an oxygen or air atmosphere, first heat at a heating rate of 1.5 - 10 °C / min to 200 - 600 °C, pre-sinter for 1 - 5 h, then heat at a heating rate of 5 - 20 °C / min to 600 - 850 °C, sinter for 5 - 20 h, and finally, cool to room temperature at a rate of 1 - 20 °C / min; obtain the sintered element-doped single-crystal morphology high-nickel ternary layered cathode material.
[0015] Preferably, in step (1), the precursor of the high-nickel ternary layered cathode material is a nickel-cobalt-manganese hydroxide precursor with the chemical formula Ni x Co y Mn z (OH) 2 , where x ≥ 0.6, y > 0, z > 0, x + y + z = 1; or the precursor of the high-nickel ternary layered cathode material is a nickel-cobalt-manganese carbonate precursor with the chemical formula Nix Co y Mn z CO 3 , wherein x≥0.6, y>0, z>0, and x + y + z = 1. Further preferably, the high-nickel ternary layered cathode material precursor is Ni x Co y Mn z (OH) 2 , where x≥0.8, y>0, z>0, and x + y + z = 1.
[0016] Preferably, in step (1), the molar ratio of the precursor to the halide salt is 1:0.02 - 0.05.
[0017] Preferably, the lithium source is at least one of LiOH, LiOH·H 2 O, Li 2 CO 3 .
[0018] Preferably, in step (1), the molar ratio of the precursor to the lithium source is 1:1.05 - 1.15.
[0019] Preferably, when A is Li in the halide salt A-X, the molar ratio of the precursor to the lithium source is 1:1.0 - 1.1.
[0020] Preferably, in step (1), the ball milling and mixing method is one of dry milling or wet milling with ethanol.
[0021] Preferably, in step (2), the sintering atmosphere is an oxygen atmosphere.
[0022] For the lithium-ion battery of the present invention, the cathode material of the battery is the single-crystal-shaped high-nickel ternary layered cathode material of the present invention.
[0023] Invention mechanism: The present invention uses a high-temperature solid-phase sintering method assisted by a halide as a dopant to synthesize single-crystal Li 1-α Ni x Co y Mn z A α O 2-α X α . By regulating the heating rate and cooling rate in multiple calcination stages, prolonging the heating time in the low-temperature stage, and shortening the heating and holding time in the high-temperature stage, Li +Diffusing sufficiently at a lower temperature is beneficial to reducing the adhesion and agglomeration of single-crystal particles and alleviating the crystal structure defects of the single-crystal high-nickel cathode material. In addition, introducing low-melting-point halides as sintering fluxes and dopants during the sintering process can, on the one hand, reduce the sintering temperature, accelerate the growth of single-crystal particles, improve the dispersibility of single-crystal particles, without introducing other impurities and avoiding additional water-washing processes; on the other hand, it can reduce the surface energy of the material, adjust the morphology of the single-crystal high-nickel material, introduce doping elements to increase the lithium layer spacing, improve the crystal structure stability of the material, and improve the electrochemical performance of the single-crystal high-nickel ternary layered cathode material.
[0024] Beneficial effects: Compared with the prior art, the present invention has the following remarkable advantages: (1) Due to the doping of halide salts, the structural stability of the high-nickel ternary layered cathode material of the present invention is enhanced, and the electrochemical performance is improved; (2) Under the condition of 0.1C rate, within the voltage range of 2.8 - 4.3V, the initial discharge capacity of the high-nickel ternary layered cathode material of the present invention is greater than 200 mAh g -1 , and the capacity retention rate is greater than 93% after 200 charge-discharge cycles (under the condition of 1C rate); (3) The preparation method of high-temperature solid-phase sintering with regulated heating rate provided by the present invention is simple, and the sintering conditions can be adjusted on the existing mature production line process, without the need for an additional water-washing step to remove the flux, and is suitable for large-scale production. Description of the Drawings
[0025] Figure 1 SEM image of the single-crystal high-nickel cathode material prepared in Example 1 of the present invention;
[0026] Figure 2 SEM image of the polycrystalline high-nickel cathode material prepared in Comparative Example 1 of the present invention;
[0027] Figure 3 XRD spectra and their partial enlarged views of the high-nickel cathode materials prepared in Comparative Example 1 and Example 1 of the present invention;
[0028] Figure 4 Cycling curve of the battery assembled with the single-crystal high-nickel cathode material prepared in Example 1 of the present invention within the voltage range of 2.8 - 4.3V;
[0029] Figure 5 Cycling curve of the battery assembled with the polycrystalline high-nickel cathode material prepared in Comparative Example 1 of the present invention within the voltage range of 2.8 - 4.3V;
[0030] Figure 6 SEM image of the single-crystal high-nickel cathode material prepared in Example 2 of the present invention;
[0031] Figure 7 SEM image of the single-crystal high-nickel cathode material prepared in Example 3 of the present invention;
[0032] Figure 8 SEM image of the single-crystal high-nickel cathode material prepared in Example 4 of the present invention;
[0033] Figure 9 SEM image of the single-crystal high-nickel cathode material prepared in Example 5 of the present invention;
[0034] Figure 10 SEM image of the single-crystal high-nickel cathode material prepared in Example 6 of the present invention;
[0035] Figure 11 SEM image of the single-crystal high-nickel cathode material prepared in Example 7 of the present invention;
[0036] Figure 12 SEM image of the single-crystal high-nickel cathode material prepared in Example 8 of the present invention;
[0037] Figure 13 XRD spectrum and its partial enlarged view of the high-nickel cathode material prepared in Example 7 and Comparative Example 1 of the present invention;
[0038] Figure 14 XRD spectrum and its partial enlarged view of the high-nickel cathode material prepared in Example 8 and Comparative Example 1 of the present invention;
[0039] Figure 15 Cycling curve of the battery assembled with the single-crystal high-nickel cathode material prepared in Example 7 of the present invention in the voltage range of 2.8 - 4.3V;
[0040] Figure 16 Cycling curve of the battery assembled with the single-crystal high-nickel cathode material prepared in Example 8 of the present invention in the voltage range of 2.8 - 4.3V;
[0041] Figure 17 SEM image of the single-crystal high-nickel cathode material prepared in Comparative Example 2 of the present invention;
[0042] Figure 18 Cycling curve of the battery assembled with the single-crystal high-nickel cathode material prepared in Comparative Example 2 of the present invention in the voltage range of 2.8 - 4.3V. Detailed implementation manners
[0043] The technical solutions of the present invention will be further described below in conjunction with the embodiments.
[0044] The assembly and testing methods of CR2032 button batteries in each embodiment and comparative example of the present invention are as follows: The prepared cathode material, acetylene black (Super P), and polyvinylidene fluoride (PVDF) are mixed evenly according to a mass ratio of 8:1:1. After sufficient grinding, an appropriate amount of N-methyl-di-ethylpyrrolidone (NMP) is added to make a slurry, which is then coated on aluminum foil and dried in vacuum at 90 °C for 12 h. After the sample is cooled to room temperature, it is taken out, and the aluminum foil loaded with the slurry is cut into circular pole pieces with a diameter of 11 mm using a cutting machine, and its mass is weighed for use as the cathode; the cathode pole piece is placed into the cathode shell, covered with a separator (model Celgard 2500 polypropylene microporous membrane), and a lithium sheet, gasket, and spring sheet are placed in sequence, and 100 mL of electrolyte (1M LiPF 6 dissolved in a mixed solvent with a volume ratio of EC to EMC of 3:7) is dropped in, and then the anode shell is covered, and the battery is encapsulated using a sealing machine (model MSK-E110 pressure-controlled electric sealing machine). The CR2032 button battery is assembled in a glove box under a high-purity argon atmosphere.
[0045] Example 1
[0046] The halide-assisted single-crystal morphology high-nickel ternary layered cathode material of the present invention has the chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 , and the preparation method includes the following steps:
[0047] (1) Mixing materials: The hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , LiOH·H 2 O, and the dopant LiF are weighed according to a molar ratio of 1:1.08:0.02 and manually ground for preliminary mixing, and then placed in a zirconia ball milling tank, and the mixture is further mixed evenly using a planetary ball mill. The rotation speed is set to 500 rpm, and the mixing time is 3 h to obtain a mixed material.
[0048] (2) Sintering: The obtained mixed material is placed in an Al 2 O 3 porcelain boat and sintered using a tube furnace. The oxygen flow rate is set to 300 mL / min. The tube furnace is first heated to 450 °C at a heating rate of 3 °C / min and held for 5 h, then heated to 780 °C at a heating rate of 10 °C / min and held for 12 h, and then cooled to room temperature at a cooling rate of 5 °C / min to obtain an F-doped single-crystal high-nickel cathode material.
[0049] Electrochemical test: Using a Blue Electric Battery Test System model CT3002A, the test channel range is 5V and 10mA, the recording time is 10s, and the battery is subjected to charge-discharge cycle testing at room temperature of 25°C. The specific test conditions are as follows: The assembled button battery is left standing in air for 24h, the voltage test range is 2.8 - 4.3V, and it is first charged and discharged for activation in two cycles with a constant charge-discharge current of 0.1C (1C = 200mA g -1 ) and the remaining several cycles are tested with a 1C rate.
[0050] Example 2
[0051] The halide-assisted single-crystal morphology high-nickel ternary layered cathode material described in the present invention has the chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 1.95 F 0.05 , and the preparation method includes the following steps:
[0052] (1) Mixing: Weigh the hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , LiOH·H 2 O and the dopant LiF in a molar ratio of 1:1.12:0.05, manually grind and preliminarily mix them, then place them in a zirconia ball milling tank, and further mix the mixture evenly using a planetary ball mill. Set the rotation speed to 500rpm and the mixing time to 3h to obtain a mixed material.
[0053] (2) Sintering: Place the obtained mixed material in an Al 2 O 3 ceramic boat and sinter it using a tube furnace. Set the oxygen flow rate to 300mL / min. The tube furnace first heats up to 450°C at a heating rate of 3°C / min and holds for 5h, then heats up to 800°C at a heating rate of 10°C / min and holds for 12h, and then cools down to room temperature at a cooling rate of 5°C / min to obtain the F-doped single-crystal high-nickel cathode material.
[0054] Electrochemical test: Using a Blue Electric Battery Test System model CT3002A, the test channel range is 5V and 10mA, the recording time is 10s, and the battery is subjected to charge-discharge cycle testing at room temperature of 25°C. The specific test conditions are as follows: The assembled button battery is left standing in air for 24h, the voltage test range is 2.8 - 4.3V, and it is first charged and discharged for activation in two cycles with a constant charge-discharge current of 0.1C (1C = 200mA g -1 ) and the remaining several cycles are tested with a 1C rate.
[0055] Example 3
[0056] The halide-assisted single-crystal morphology high-nickel ternary layered cathode material described in the present invention has a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 , and the preparation method includes the following steps:
[0057] (1) Mixing materials: Weigh the hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , LiOH·H 2 O and the dopant LiF according to a molar ratio of 1:1.15:0.02, manually grind and preliminarily mix them, then place them in a zirconia ball milling tank, and use a planetary ball mill to further mix the mixture evenly. Set the rotation speed to 500 rpm and the mixing time to 3 h to obtain a mixed material.
[0058] (2) Sintering: Place the obtained mixed material in an Al 2 O 3 ceramic boat, and use a tube furnace for sintering. Set the oxygen flow rate to 300 mL / min. First, heat the tube furnace from room temperature to 450 °C at a heating rate of 1.5 °C / min and hold for 5 h, then heat it to 780 °C at a heating rate of 10 °C / min and hold for 12 h, and then cool it to room temperature at a cooling rate of 5 °C / min to obtain the F-doped single-crystal high-nickel cathode material.
[0059] Electrochemical test: Use a LAND CT3002A battery test system, the test channel range is 5 V and 10 mA, and the recording time is 10 s. Perform charge and discharge cycle tests on the battery at room temperature of 25 °C. The specific test conditions are as follows: After the assembled coin cell is left standing in the air for 24 h, the voltage test range is 2.8 - 4.3 V. First, charge and discharge and activate it for two cycles with a constant charge and discharge current of 0.1 C (1 C = 200 mA g -1 ), and perform cycle tests for the remaining several cycles at a 1 C rate.
[0060] Example 4
[0061] The halide-assisted single-crystal morphology high-nickel ternary layered cathode material described in the present invention has a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 , and the preparation method includes the following steps:
[0062] (1) Mixing materials: Weigh the hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 , LiOH·H 2 O and dopant LiF are weighed according to a molar ratio of 1:1.05:0.02 and manually ground for preliminary mixing, and then placed in a zirconia ball milling jar. The mixture is further mixed evenly by using a planetary ball mill. The rotation speed is set at 500 rpm and the mixing time is 3 h to obtain a mixed material.
[0063] (2) Sintering: The obtained mixed material is placed in an Al 2 O 3 ceramic boat and sintered by using a tube furnace. The oxygen flow rate is set at 300 mL / min. The tube furnace is first heated to 450 °C at a heating rate of 10 °C / min and held for 5 h, then heated to 780 °C at a heating rate of 10 °C / min and held for 12 h, and then cooled to room temperature at a cooling rate of 5 °C / min to obtain an F-doped single-crystal high-nickel cathode material.
[0064] Electrochemical test: Use a LAND CT3002A battery test system. The test channel range is 5 V and 10 mA, and the recording time is 10 s. The battery is subjected to charge-discharge cycle tests at room temperature of 25 °C. The specific test conditions are as follows: The assembled coin cell is left standing in air for 24 h. The voltage test range is 2.8 - 4.3 V. First, it is charged and discharged for two activation cycles with a constant charge-discharge current of 0.1 C (1 C = 200 mA g -1 ), and the remaining several cycles are tested by cycling at a 1 C rate.
[0065] Example 5
[0066] The halide-assisted single-crystal morphology high-nickel ternary layered cathode material described in the present invention has the chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 , and the preparation method includes the following steps:
[0067] (1) Mixing materials: The hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , LiOH·H 2 O and dopant LiF are weighed according to a molar ratio of 1:1.06:0.02 and manually ground for preliminary mixing, and then placed in a zirconia ball milling jar. The mixture is further mixed evenly by using a planetary ball mill. The rotation speed is set at 500 rpm and the mixing time is 3 h to obtain a mixed material.
[0068] (2) Sintering: The obtained mixed material is placed in an Al 2 O 3In a porcelain boat, sintering was carried out using a tube furnace. The oxygen flow rate was set at 300 mL / min. The tube furnace was first heated at a heating rate of 3 °C / min to 450 °C and held for 5 h, then heated to 780 °C at a heating rate of 20 °C / min and held for 12 h, and then cooled to room temperature at a cooling rate of 5 °C / min to obtain the F-doped single-crystal high-nickel cathode material.
[0069] Electrochemical test: Using a Lanhe battery test system model CT3002A, the test channel range was 5 V and 10 mA, and the recording time was 10 s. The battery was subjected to charge-discharge cycle tests at room temperature of 25 °C. The specific test conditions were as follows: The assembled coin cell was left standing in air for 24 h, the voltage test range was 2.8 - 4.3 V, and it was first charged and discharged actively for two cycles with a constant charge-discharge current of 0.1 C (1 C = 200 mA g -1 ), and the remaining several cycles were tested by cycling at a 1 C rate.
[0070] Example 6
[0071] The halide-assisted single-crystal morphology high-nickel ternary layered cathode material described in the present invention has the chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 , and the preparation method includes the following steps:
[0072] (1) Mixing: The hydroxide precursors Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , LiOH·H 2 O and the dopant LiF were weighed according to a molar ratio of 1:1.10:0.02, manually ground and preliminarily mixed, and then placed in a zirconia ball milling tank. The mixture was further mixed evenly using a planetary ball mill, the rotation speed was set at 500 rpm, and the mixing time was 3 h to obtain the mixed material.
[0073] (2) Sintering: The obtained mixed material was placed in an Al 2 O 3 porcelain boat, and sintering was carried out using a tube furnace. The oxygen flow rate was set at 300 mL / min. The tube furnace was first heated at a heating rate of 3 °C / min to 450 °C and held for 5 h, then heated to 780 °C at a heating rate of 5 °C / min and held for 12 h, and then cooled to room temperature at a cooling rate of 5 °C / min to obtain the F-doped single-crystal high-nickel cathode material.
[0074] Electrochemical test: Using a Lanhe battery test system model CT3002A, the test channel range is 5V and 10mA, the recording time is 10s, and the charge-discharge cycle test of the battery is carried out at room temperature of 25°C. The specific test conditions are as follows: The assembled coin cell is left standing in the air for 24h, the voltage test range is 2.8 - 4.3V, and it is first charged and discharged for activation in two cycles with a constant charge-discharge current of 0.1C (1C = 200mA g -1 ) and the remaining several cycles are tested by cycling at a 1C rate.
[0075] Example 7
[0076] The halide-assisted single-crystal morphology high-nickel ternary layered cathode material described in the present invention has the chemical formula Li 0.98 Na 0.02 Ni 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 , and the preparation method includes the following steps:
[0077] (1) Mixing: The hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , LiOH·H 2 O and the dopant NaF are weighed according to a molar ratio of 1:1.10:0.02 and manually ground for preliminary mixing, and then placed in a zirconia ball milling jar. The mixture is further mixed evenly by using a planetary ball mill, the rotation speed is set to 500rpm, and the mixing time is 3h to obtain a mixed material.
[0078] (2) Sintering: The obtained mixed material is placed in an Al 2 O 3 porcelain boat and sintered by using a tube furnace. The oxygen flow rate is set to 300mL / min. The tube furnace is first heated to 450°C at a heating rate of 3°C / min and held for 5h, then heated to 780°C at a heating rate of 10°C / min and held for 12h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a single-crystal high-nickel cathode material doped with F and Na.
[0079] Electrochemical test: Using a Lanhe battery test system model CT3002A, the test channel range is 5V and 10mA, the recording time is 10s, and the charge-discharge cycle test of the battery is carried out at room temperature of 25°C. The specific test conditions are as follows: The assembled coin cell is left standing in the air for 24h, the voltage test range is 2.8 - 4.3V, and it is first charged and discharged for activation in two cycles with a constant charge-discharge current of 0.1C (1C = 200mA g -1 ) and the remaining several cycles are tested by cycling at a 1C rate.
[0080] Example 8
[0081] For the halide-assisted single-crystal morphology high-nickel ternary layered cathode material of the present invention, the chemical formula is Li 0.98 K 0.0 2 Ni 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 , and the preparation method includes the following steps:
[0082] (1) Mixing materials: Weigh the hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , LiOH·H 2 O and the dopant KF according to the molar ratio of 1:1.10:0.02, manually grind and preliminarily mix them, then place them in a zirconia ball milling tank, and use a planetary ball mill to further mix the mixture evenly. Set the rotation speed to 500 rpm and the mixing time to 3 h to obtain a mixed material.
[0083] (2) Sintering: Place the obtained mixed material in an Al 2 O 3 porcelain boat, and use a tube furnace for sintering. Set the oxygen flow rate to 300 mL / min. First, heat the tube furnace from room temperature to 450 °C at a heating rate of 3 °C / min and hold for 5 h, then heat it to 780 °C at a heating rate of 10 °C / min and hold for 12 h, and then cool it to room temperature at a cooling rate of 5 °C / min to obtain an F- and K-doped single-crystal high-nickel cathode material.
[0084] Electrochemical test: Use a LAND CT3002A battery test system, the test channel range is 5 V and 10 mA, and the recording time is 10 s. Perform charge and discharge cycle tests on the battery at room temperature of 25 °C. The specific test conditions are as follows: The assembled coin cell is left standing in the air for 24 h, the voltage test range is 2.8 - 4.3 V, first charge and discharge and activate it for two cycles with a constant charge and discharge current of 0.1 C (1 C = 200 mA g -1 ), and the remaining several cycles are tested with a 1 C rate.
[0085] Comparative Example 1
[0086] The preparation method of the LiNi 0.8 Co 0.1 Mn 0.1 O 2 single-crystal high-nickel cathode material includes the following steps:
[0087] (1) Mixing materials: Weigh the hydroxide precursor Ni 0.8Co 0.1 Mn 0.1 (OH) 2 、LiOH·H 2 O were weighed according to a molar ratio of 1:1.10 and preliminarily mixed by manual grinding, and then placed in a zirconia ball milling jar. The mixture was further mixed evenly by using a planetary ball mill, with the rotation speed set at 500 rpm and the mixing time of 3 h to obtain a mixed material.
[0088] (2) Sintering: The obtained mixed material was placed in an Al 2 O 3 porcelain boat and sintered by using a tube furnace. The oxygen flow rate was set at 300 mL / min. The tube furnace was first heated to 450 °C at a heating rate of 3 °C / min and held for 5 h, then heated to 780 °C at a heating rate of 10 °C / min and held for 12 h, and then cooled to room temperature at a cooling rate of 5 °C / min to obtain a polycrystalline high-nickel cathode material.
[0089] Electrochemical test: Using a Lanhe battery test system of model CT3002A, the test channel range was 5 V and 10 mA, and the recording time was 10 s. The battery was subjected to charge-discharge cycle tests at room temperature of 25 °C. The specific test conditions were as follows: The assembled coin cell was left standing in air for 24 h, the voltage test range was 2.8 - 4.3 V, and it was first charged and discharged for two activation cycles with a constant charge-discharge current of 0.1C (1C = 200 mA g -1 ), and the remaining several cycles were tested by cycling at a 1C rate.
[0090] Comparative Example 2
[0091] LiNi 0.8 Co 0.1 Mn 0.1 O 2 The preparation method of the single-crystal high-nickel cathode material comprises the following steps:
[0092] Mixing materials: The hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 、LiOH·H 2 O were weighed according to a molar ratio of 1:1.15 and preliminarily mixed by manual grinding, and then placed in a zirconia ball milling jar. The mixture was further mixed evenly by using a planetary ball mill, with the rotation speed set at 500 rpm and the mixing time of 3 h to obtain a mixed material.
[0093] Sintering: The obtained mixed material was placed in an Al 2 O 3In a porcelain boat, sintering was carried out using a tube furnace. The oxygen flow rate was set at 300 mL / min. The tube furnace was first heated at a heating rate of 3 °C / min to 450 °C and held for 5 h, then heated to 850 °C at a heating rate of 10 °C / min and held for 15 h. Subsequently, it was cooled to room temperature at a cooling rate of 5 °C / min to obtain a high-nickel cathode material with severely agglomerated and adhered primary particles.
[0094] Electrochemical test: Using a Lanhe battery test system model CT3002A, the test channel range was 5 V and 10 mA, and the recording time was 10 s. The battery was subjected to charge-discharge cycle testing at room temperature of 25 °C. The specific test conditions were as follows: The assembled coin cell was left standing in air for 24 h, the voltage test range was 2.8 - 4.3 V, and it was first charged and discharged actively for two cycles with a constant charge-discharge current of 0.1C (1C = 200 mA g -1 ), and the remaining several cycles were tested by cycling at a 1C rate.
[0095] Figure 1 SEM images of the single-crystal high-nickel cathode material prepared in Example 1, with an average particle size distribution of 2 - 3 μm, 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 and the secondary particle average particle size distribution of the polycrystalline high-nickel cathode material prepared in Comparative Example 1 was 2 - 3 μm; by analyzing Figure 2 LiNi 0.8 Co 0.1 Mn 0.1 O 2 it can be concluded that introducing LiF as a flux can reduce the eutectic point of the mixture during the synthesis process, promote the uniform diffusion of Li Figure 1 and Figure 2 and the growth of single-crystal particles, and obtain a high-nickel cathode material with a good dispersive single-crystal morphology. +
[0096] Figure 3 XRD spectra and their partial enlarged views of the high-nickel cathode materials prepared in Comparative Example 1 and Example 1. It can be seen from the figure that both materials conform to the standard hexagonal α-NaFeO 2 structure. The intensity ratio I (003) / I (104) of the two main peaks (003) and (104) can, to a certain extent, represent the degree of cation mixing in the sample lattice, that is, the larger the ratio, the relatively lower the degree of cation mixing. I (003) / I (104) If the value is greater than 1.2, it indicates that the layered structure of the material is ordered. Both Comparative Example 1 and Example 1 have good layered structures. The doping of F element replaces O element to form local octahedra of halides, enhancing the TM-F bond force, expanding the distance between lithium layer and oxygen layer, and accelerating the Li + transport, resulting in an increase in the lattice constants of both a-axis and c-axis; to maintain charge balance, the introduction of F - will cause the partial transition of Ni 3+ to Ni 2+ , making the mixing of Li + / Ni 2+ more serious. However, a certain degree of anti-site defects is beneficial to the structural stability.
[0097] Figure 4 For the electrochemical performance test of the LiNi 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 single-crystal high-nickel cathode material prepared in Example 1, under the condition of constant current charge and discharge at 2.8~4.3V and 1C rate, the capacity retention rate after 200 cycles is as high as 96%. Figure 5 For the electrochemical performance test of the LiNi 0.8 Co 0.1 Mn 0.1 O 2 polycrystalline high-nickel cathode material prepared in Comparative Example 1, under the same test conditions, the capacity retention rate after 200 cycles is 86.2%. It can be seen that the single-crystal high-nickel cathode material with regular morphology prepared by doping 0.02mol of F element enhances the crystal structure stability of the material, inhibits the generation of microcracks during cycling, and improves the cycling stability of the material.
[0098] Figure 6 For the SEM image of the LiNi 0.8 Co 0.1 Mn 0.1 O 1.95 F 0.05 single-crystal high-nickel cathode material prepared in Example 2, the average particle size is distributed around 1μm. The introduction of more LiF and excessive lithium source requires increasing the calcination temperature to promote the volatilization of the excessive lithium source, reducing the surface energy of single-crystal particles, and realizing the dispersion of particles. However, the increase in temperature will also cause particle fragmentation and serious irregularity of the morphology.
[0099] Figure 7 and Figure 8 are the LiNi 0.8 Co 0.1 Mn 0.1 O 1.98 F0.02 SEM images of the single-crystal high-nickel cathode material, with an average particle size distribution of about 1 μm. Compared with Example 1, reducing the heating rate from room temperature to low temperature results in an overly long heating time in the low-temperature section, a decrease in the particle size of the single-crystal particles, and the particles tend to agglomerate. Increasing the heating rate from room temperature to low temperature shortens the heating time in the low-temperature section, resulting in incomplete Li + diffusion and incomplete growth of small single-crystal particles.
[0100] Figures 9 - 10 For the LiNi 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 SEM images of the single-crystal high-nickel cathode material, with an average particle size distribution of 2 - 3 μm. Compared with Example 1, increasing or decreasing the heating rate from low temperature to high temperature has little effect on the particle size and dispersion degree of the single-crystal particles.
[0101] Figure 11 For the Li 0.98 Na 0.02 Ni 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 SEM images of the single-crystal high-nickel cathode material, with an average particle size distribution of 1 - 2 μm. Compared with Comparative Example 1, using NaF as a flux reduces the eutectic point, resulting in single-crystal particles with regular morphology and good dispersion. Compared with Example 1, the melting point of NaF is higher than that of LiF, and the increased eutectic temperature limits the growth of Li + diffusion during the initial growth stage, restricting the growth of single-crystal particles and resulting in smaller particle sizes. Figure 12 For the Li 0.98 K 0.02 Ni 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 SEM images of the single-crystal high-nickel cathode material, with an average particle size distribution of 1 - 2 μm. Compared with Comparative Example 1, using KF as a flux reduces the eutectic point, resulting in single-crystal particles with regular morphology and good dispersion. Compared with Example 1, the single-crystal particles prepared using KF as a flux have smaller particle sizes. Different halides as fluxes can achieve specific adsorption on different crystal planes, controlling the specific morphology and particle size of single crystals.
[0102] Figure 13 and Figure 14 XRD spectra and their partial enlarged views of the high-nickel cathode materials prepared from Comparative Example 1 and Example 7, and Comparative Example 1 and Example 8. It can be seen from the figure that all materials conform to the standard hexagonal α-NaFeO2 Structure, the peak intensity ratio I of two main peaks (003) and (104) (003) / I (104) value can, to a certain extent, represent the degree of cation mixing in the sample lattice. That is, the larger the ratio, the relatively lower the degree of cation mixing. I (003) / I (104) value greater than 1.2 indicates that the layered structure of the material is ordered. Comparative Example 1, Example 7, and Example 8 all have a good layered structure. The doping of F element to replace O element forms local octahedra of halides, enhancing the TM-F bond force, expanding the spacing between the lithium layer and the oxygen layer, and accelerating the Li + transport. The doping of Na element and K element to replace the Li layer plays a role of the pillar effect, inhibiting cation mixing, and neutralizing the Ni - induced by the introduction of F 3+ partial transition to Ni 2+ . The use of NaF and KF as dopants increases the lattice constants of both the a-axis and the c-axis. Due to the relatively large radius of K + and it cannot be completely incorporated into the Li layer, compared with Example 7, its degree of lithium-nickel mixing is heavier, and the deviation degree of the (003) and (104) crystal plane angles is larger.
[0103] Figure 15 For the electrochemical performance test of the Li 0.98 Na 0.02 Ni 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 single crystal high-nickel cathode material prepared in Example 7, under the condition of constant current charge and discharge at 2.8 - 4.3V, at a 1C rate, the capacity retention rate after 200 cycles is as high as 93.9%, higher than 86.2% of Comparative Example 1 under the same test conditions. Figure 16 For the electrochemical performance test of the Li 0.9 8 K 0.02 Ni 0.8 Co 0.1 Mn 0.1 O 1.98 F 0.02 single crystal high-nickel cathode material prepared in Example 8, under the condition of constant current charge and discharge at 2.8 - 4.3V, at a 1C rate, the capacity retention rate after 200 cycles is as high as 93.0%, higher than 86.2% of Comparative Example 1 under the same test conditions.
[0104] Figure 17 For LiNi 0.8 Co 0.1 Mn 0.1 O2 SEM images of the high-nickel cathode material, with the average particle size of the primary particles distributed between 2 and 3 μm; compared with Comparative Example 1, without introducing halides as dopants and fluxes, increasing the calcination temperature, and introducing an excessive lithium source to offset the volatilization of lithium at high temperatures, the obtained single-crystal particles show a serious agglomeration state. Figure 18 For Comparative Example 2 under the conditions of constant current charge and discharge at 2.8 - 4.3 V and a 1C rate, the capacity retention rate after 200 cycles is 76.5%, which is much lower than 96% of Example 1.
[0105] Therefore, by introducing halides as fluxes and dopants, and simultaneously adopting a high-temperature solid-state sintering technique with controlled heating rate, a high-nickel ternary layered cathode material with regular and monodisperse morphology can be prepared. The introduction of halides can act as a flux to reduce the energy consumption of high-temperature calcination to obtain single-crystal primary particles with uniform particle size, regular morphology, and good dispersion, and can also act as a dopant to enhance the stability of the crystal structure and improve the electrochemical cycling stability.
Claims
1. A halide-assisted single crystal morphology high nickel ternary layered cathode material, characterized in that: Its chemical formula is; Li 1-α Ni x Co y Mn z A α O 2-β X β , where 0.6 ≤ x < 1, 0 < y ≤ 0.2, 0 < z ≤ 0.2, 0 < α ≤ 0.05, 0 < β ≤ 0.05, x + y + z = 1, A is at least one of Li, Na, K, Rb, Cs, X is at least one of F, Cl, Br, I, and the material has a monodisperse morphology; the primary sintering conditions during the sintering process of the material are: heating at a heating rate of 1.5 - 10 °C / min to 200 - 600 °C, pre-sintering for 1 - 5 h, then heating at a heating rate of 5 - 20 °C / min to 600 - 850 °C, sintering for 5 - 20 h, and finally, cooling to room temperature at a rate of 1 - 20 °C / min; the dopant and flux during the sintering process are halide salts.
2. The halide-assisted single crystal high nickel ternary layered cathode material according to claim 1, characterized in that: The halide salt is AX, A is at least one of Li, Na, and K, and X is at least one of F, Cl, and Br.
3. The halide-assisted single crystal high nickel ternary layered cathode material according to claim 1, characterized in that: During the sintering process of the material, the temperature is first raised to 430-550°C at a heating rate of 1.5-10°C / min and pre-fired for 3-5h, then raised to 700-800°C at a heating rate of 5-10°C / min and sintered for 8-15h; the cooling rate of the final cooling process is 2-10°C / min.
4. A method for preparing the halide-assisted single crystal high nickel ternary layered cathode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing a nickel-cobalt-manganese ternary precursor, a lithium source, and a halide salt uniformly with a high-speed ball mill to obtain a mixture; (2) placing the mixture in a tubular furnace, under an oxygen or air atmosphere, first heating the mixture to 200-600° C. at a heating rate of 1.5-10° C. / min, pre-sintering for 1-5 h, then heating the mixture to 600-850° C. at a heating rate of 5-20° C. / min, sintering for 5-20 h, and finally cooling the mixture to room temperature at a rate of 1-20° C. / min; obtaining a high-nickel ternary layered positive electrode material with a single crystal morphology doped with elements after sintering.
5. The method of halide-assisted single crystal high nickel ternary layered cathode material according to claim 4, characterized in that: In step (1), the high-nickel ternary layered cathode material precursor is a nickel-cobalt-manganese hydroxide precursor, with a chemical formula of Ni x Co y Mn z (OH)2, wherein x≥0.6, y>0, z>0, x+y+z=1; or the high-nickel ternary layered cathode material precursor is a nickel-cobalt-manganese carbonate precursor, the chemical formula of which is Ni x Co y Mn z CO3, where x≥0.6, y>0, z>0, x+y+z=1.
6. The method of halide-assisted single crystal high nickel ternary layered cathode material according to claim 4, characterized in that: The high nickel ternary layered cathode material precursor is Ni x Co y Mn z (OH)2, x≥0.8, y>0, z>0, x+y+z=1.
7. The method of halide-assisted single crystal high nickel ternary layered cathode material according to claim 4, characterized in that: The molar ratio of the precursor to the halide salt is 1:0.02-0.
05.
8. The method of halide-assisted single crystal high nickel ternary layered cathode material according to claim 4, characterized in that: In step (1), the molar ratio of the precursor to the lithium source is 1:1.05-1.
15.
9. The method of halide-assisted single crystal high nickel ternary layered cathode material according to claim 7, characterized in that: In the halide salt AX, when A is Li, the molar ratio of the precursor to the lithium source is 1:1.0-1.
1.
10. A lithium ion battery, characterized in that: The positive electrode material of the battery is a high-nickel ternary layered positive electrode material with a single crystal morphology as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Single-crystal high-nickel ternary positive electrode material and preparation method thereof
CN109768231A
Cited By
High-nickel single-crystal positive electrode material as well as preparation method and application thereof
CN120553773A